Design and Characterization of Ultrasonic Langevin Transducer 20 kHz Using a Stepped Horn Front-Mass - Aisyah Nurul Khairiyah; Gandi Sugandi; Deddy Kurniadi (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Ultrasonication is a method that is widely used in various fields. One of its applications is to accelerate the process of homogenization, emulsification, and extraction. In the ultrasonicator system, the transducer is an extremely important device. The resonant frequency, longitudinal vibration amplitude, and electromechanical coupling are the targets in designing an ultrasonic transducer. In this investigation, the main contribution was the development of a simple and effective method for mechanically tuning the resonant frequency of the transducer by adding mass to the front end of the mass or stepped horn. This study also aimed to obtain optimal results by examining the effects of geometric dimensions, bolt prestress, stress distribution, resonant frequency, amplitude, and electrical impedance. The ultrasonic transducer model was designed with a resonant frequency of 20 kHz and simulated using the finite element analysis. The steps involved included calculating the dimensions and geometric structure of the transducer, modeling using the finite-element method, and experimental validation. The simulation results and measurements showed that the series resonant frequency, electrical impedance, and effective electromechanical coupling of the Model-4 transducer 16∙13 mm radiator configuration were 20.15 kHz, 100 Ω, and 0.2229 from the simulation results, and 20.17 kHz, 24.91 Ω, and 0.2033 from the measurement results. A percentage difference, or relative error, of 0.1% was obtained between the simulation and the experimental results for this Model-4 with bolt prestressing at 15 kN.